Academician Semyon Semyonovich Girgolav (1881–1957) (to the 140th anniversary of the birth) - B. N. Kotiv; Al. A. Kurygin; I. I. Dzidzava; V. V. Semenov (Вестник хирургии имени И.И. Грекова, 2021)
Professor Semyon Semyonovich Girgolav was born on February 2 (14), 1881 in Tiflis (Tbilisi) in a large family of the hereditary honorary citizen of St. Petersburg Semyon Gavrilovich Girgolav. In 1899, he graduated from the Second St. Petersburg Classical Gymnasium with a silver medal and immediately entered the Imperial Military Medical Academy, from which he graduated with honors in 1904. Under the guidance of M. S. Subbotin, S. S. Girgolav prepared and in 1907 successfully defended his doctoral dissertation «Experimental data on the use of an isolated omentum in abdominal surgery». In 1912, Semyon Semyonovich was elected by the Conference of the Academy as a privatdozent of the general surgery clinic, and in 1914, he was confirmed as a senior assistant of the clinic. In the 1920/21 academic year, S. S. Girgolav introduced mandatory practical classes in general surgery for the first time in our country, where students studied and mastered the methods of asepsis and antiseptics, mastered the methods of examining patients with surgical diseases, methods of applying various bandages and transportation splints, techniques for temporary hemostasis, etc. In 1932, Semyon Semyonovich was appointed Deputy Director for the scientific part of the Leningrad Research Institute of Traumatology and Orthopedics (now the Russian Research Institute of Traumatology and Orthopedics named after R. R. Vreden). In the pre-war years, the main direction of scientific research of S. S. Girgolav and his staff in the hospital surgery clinic was the study of the regularities of the wound process and wound healing in surgical pathology. S. S. Girgolav applied much efforts and energy to the problems of traumatology. He developed the technique of a number of original surgical operations for acute fractures of long bones, the habitual dislocation of the shoulder joint. Semyon Semyonovich’s scientific heritage is great and multifaceted. He has published more than 140 scientific papers on general, military and thoracic surgery, traumatology, neurosurgery, surgical endocrinology and oncology, combustiology, pathology and therapy of frostbites and burns. Under the supervision of S. S. Girgolav, more than 20 doctoral and 45 candidate theses were prepared and defended. For outstanding services to the Motherland in peace and war, S. S. Girgolav was awarded two Orders of Lenin, three Orders of the Red Banner, the Order of the Red Banner of Labor, the Order of the Red Star, many medals and badges of honour. Academician Semyon Semyonovich Girgolav died on January 25, 1957 in Leningrad and was buried at the Bogoslovskoe Cemetery.